The Effect of Socio-Demographic and Obstetric Factors on Early Initiation of Breastfeeding in Tegal District, Central Java - Nisa, Juhrotun; Salimo, Harsono; Budihastuti, Uki Retno (Journal of Maternal and Child Health, 2017)
Background: